Love Arabic Movement: Participatory-Based Mentoring for Learning Basic Arabic Writing for Santri at Raudlatut Thalabah Islamic Boarding School Banyuwangi - Nur Maya Badriyatul Jamroh (CENDEKIA: Jurnal Pengabdian Masyarakat, 2026)
Mastering basic Arabic writing skills (maharah al-kitabah) for Islamic boarding school students (santri) is often hindered by conventional, passive learning methods. This community service activity aims to improve basic Arabic writing skills and foster learning motivation among santri through the "Love Arabic Movement" using a participatory-based approach. The partner for this activity was Raudlatut Thalabah Islamic Boarding School in Banyuwangi, involving 40 elementary-level santri. The service method applied was Participatory Action Research (PAR), with implementation phases including preparation (needs analysis, pocket module development, and peer tutor training), implementation using the D-A-K-A framework (Demonstration, Group Action, Joint Correction, and Application) supported by Hijaiyah Flashcards and Mini Whiteboards, and evaluation (Pre-Test and Post-Test). The results showed a significant improvement in the students' technical writing skills and basic orthography. The average score increased by 28.4 points, rising from 54.2 in the Pre-Test to 82.6 in the Post-Test, with a mastery rate reaching 87.5%. Furthermore, student participation and confidence increased rapidly through peer tutoring interactions and group-based learning. This program also established an "Arabic Corner" (Zawaiyah Al-Lughah) at the boarding school as a sustainable platform to showcase and appreciate the students' written work.Abstract. Mastering basic Arabic writing skills (maharah al-kitabah) for Islamic boarding school students (santri) is often hindered by conventional, passive learning methods. This community service activity aims to improve basic Arabic writing skills and foster learning motivation among santri through the "Love Arabic Movement" using a participatory-based approach. The partner for this activity was Raudlatut Thalabah Islamic Boarding School in Banyuwangi, involving 40 elementary-level santri. The service method applied was Participatory Action Research (PAR), with implementation phases including preparation (needs analysis, pocket module development, and peer tutor training), implementation using the D-A-K-A framework (Demonstration, Group Action, Joint Correction, and Application) supported by Hijaiyah Flashcards and Mini Whiteboards, and evaluation (Pre-Test and Post-Test). The results showed a significant improvement in the students' technical writing skills and basic orthography. The average score increased by 28.4 points, rising from 54.2 in the Pre-Test to 82.6 in the Post-Test, with a mastery rate reaching 87.5%. Furthermore, student participation and confidence increased rapidly through peer tutoring interactions and group-based learning. This program also established an "Arabic Corner" (Zawaiyah Al-Lughah) at the boarding school as a sustainable platform to showcase and appreciate the students' written work.